Budowa geologiczna północnego fragmentu Wału Zielonogórskiego (okolice Przylepu) = Geological structure of north part of Wał Zielonogórski (Przylep surroundings) - Gontaszewska-Piekarz, Agnieszka; Kraiński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents detailed description of geological structure of Przylep surroundings. This area is a part of north slope of Wał Zielonogórski - glacitectonical elevation formed during warta glaciation and transformed during wisła glaciarion. Many glacitectonical disturbances (e.g. folds) and glacitectonical floats built from neogene deposits occurs Inside this elevation. On north slope of Wał Zielonogórski exists also kame-terrace. Geological structure of this area was shown on many intersection based on 60m depth bore-holes.
Keywords: Wał Zielonogórski; zaburzenia glacitektoniczne; tarasy kemowe; glacitectonical disturbances; kame-terrace